2016
DOI: 10.5505/actamedica.2016.52714
|View full text |Cite
|
Sign up to set email alerts
|

Acinetobacter Infection and Resistance Profile of Intensive Care Units In a City of Northwestern Anatolia

Abstract: Introduction:Determination of suitable antibiotics in treatment of Acinetobacter infections is through the hospital ascertaining the resistance state to bacteria causing the problem. In this study, the evaluation of antibiotics sensitivity of Acinetobacter strains isolated as infection factor in patients hospitalized in intensive care units is aimed.Methods: Acinetobacter strains isolated from the samples of patients hospitalized in the 2nd and 3rd Stage adult intensive care units of a province in in northwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
0
0
3
Order By: Relevance
“…They interpreted this situation as the development of resistance due to its frequent use as an empirical antibiotic in combination therapy over the years. 25 In our study, the rates were found to be similar, and it was observed that they were 97.8% for ciprofloxacin and 99.1% for levofloxacin, respectively. In the studies, the resistance rate of tigecycline varies considerably according to the geographical regions, and it has been reported that the resistance rate is between 7-78%.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…They interpreted this situation as the development of resistance due to its frequent use as an empirical antibiotic in combination therapy over the years. 25 In our study, the rates were found to be similar, and it was observed that they were 97.8% for ciprofloxacin and 99.1% for levofloxacin, respectively. In the studies, the resistance rate of tigecycline varies considerably according to the geographical regions, and it has been reported that the resistance rate is between 7-78%.…”
Section: Discussionsupporting
confidence: 65%
“…It is known that Acinetobacter strains rapidly develop resistance to fluoroquinolone group antibiotics. 24 Yıldız et al 25 , in a study they conducted, looked at the pattern of resistance to fluoroquinolones and showed that this rate was 98.8% to ciprofloxacin and 98.2% to levofloxacin. They interpreted this situation as the development of resistance due to its frequent use as an empirical antibiotic in combination therapy over the years.…”
Section: Discussionmentioning
confidence: 99%
“…Ulusal Antimikrobiyal Direnç Sürveyans Sistemi (UAMDSS) 2015 raporunda ise Türkiye genelinde karbapenemlere %68,39 direnç saptanmıştır (28). Ülkemizde yapılan birçok çalışmada karbapenemlere direnç %90'ın üzerinde bildirilmektedir (21,29,30). Bu raporlar ve çalışmalar son yıllarda bakteride karbapenem direnç artışını çarpıcı bir şekilde göstermektedir.…”
Section: Gereç Ve Yöntemunclassified
“…Yıldız ve ark. 2014-2015 yılları arasında erişkin YBÜ'den izole ettikleri A.baumannii izolatlarında siprofloksasine %98.8, levofloksasine %98.2 oranında direnç tespit etmişlerdir (22). Bu çalışmada kinolon grubundan sadece siprofloksasin değerlendirilmiş ve %96.1 direnç oranıyla karbapenemlerden sonra en yüksek dirence sahip ikinci ilaç olduğu görülmüştür.…”
Section: Discussionunclassified